EMPOWERING VIDEO ANALYTICS WITH AI-DRIVEN TEXT RECOGNITION IN PYTHON FOR STREAMLINED INSIGHTS - Soliev Bakhromjon Nabijonovich (Galaxy International Interdisciplinary Research Journal, 2023)
Artificial Intelligence (AI) has become an integral part of various applications, revolutionizing the way we interact with technology. This article delves into the implementation of AI in Python for text recognition from video streams. Leveraging cutting-edge techniques, the proposed system showcases the synergy between AI and Python to enhance video analysis capabilities.